The Uniforms and Banners in the Wars of Islam - Asqhar Qaedan (تاریخ اسلام)
The article, at the beginning, deals in brief, with the kind and the color of the armour of the army forces at the time of the Holy Prophet of Islam (p.b.u.h.) and the caliphs following him up until Abbasites. Then, it explains how they tried to uniform the armour of the army forces so that they could get conformity and could be distinguished from the enemy forces. Then, the article explains about two kinds of banners, namely "Liwa" and "Raayat," employed by the army forces at that time, and their use and position, as well as the differences between them in the army of Islam.